Penilaiankebersihansepertigaapikaldindingsaluranakardarismearlayer dengan menggunakan rotary instrument dengan disain convex triangular dan rectangular cross section (Hygiene assessment on apical third of root canal wall of smear layer using rotary instrument design convex triangular and rectangular cross section) - Nurni Amda; Juni Jekti N; Aries Chandra Trilaksana; Christine Anastasia Rovani; Nurhayaty Natsir; Indrya Kirana Mattulada (Journal of Dentomaxillofacial Science, 2015)
This study aim to compare the smear layer clearance on the apical third of the root canal walls instrumented withconvex triangular cross- section designed hand instruments, rectangular cross-section and convex triangular crosssectiondesigned rotary instruments. Mandibular premolars that met the inclusion criteria were divided into 3 groupsof 10 samples, and prepared using convex triangular cross section design hand instruments, convex triangular crosssectionandrectangularcross-section design rotary instruments. After preparation and drainage, the sample was cutinto halves using a stainless steel chisel, a section was randomly selected and examined using SEM with 1000 X. Thisstudy showed that the smear layer clearance of hand instrument group was the lowest compared to other two groups, the rotary instruments with rectangular cross-section design showed the highest percentage smear layer clearanceamong the three groups.It was concluded that root canal preparation using a rotary instrument design convextriangular cross section produces hygiene apical third of the canal walls of the smear layer significantly compared tomanual instruments designed convex triangular cross section and root canal preparation with a rotary instrument designof rectangular cross section produces hygiene apical third of the wall root canal of the smear layer significantlycompared convex design of triangular cross section.